Chlamydospore formation of paracoccidioides brasiliensis strain Pb-18 - Sano, A. (1990)
Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis and is known as a temperature-dependent dimorphic fungus. Even though several routes of transformation from a mycelial to yeast forms have been reported, the route via chlamydospore is the most important. At this time, conditions of temperature, nutrients, population of yeast cells and concentration of agar which influence chlamydospore formation are examined. P. brasiliensis strain Pb-18 was used in this experiment. Its yeast cells were mixed with agar media, and were cultured at various temperatures. The results were as follows: 1. At 25°C, more chlamydospores were formed in poor media than in rich ones. 2. At over 25°C, the number of chlamydospores increased in proportion to the increase in temperature. 3. Chlamydospores were most frequently formed when 106 yeast cell units were mixed with 25ml of medium. 4. One and 2.0‰ agars were the most adequate concentrations for chlamydospore formation.